Direct seeded rice: What are the benefits, potential and suitability in Haryana, India? - Deb, Proloy; Kumar, Virender; Srivastava, Amit (CGIAR System Organization, 2023)
Rice is one of the most widely grown cereal crops in India, providing primary nutrition as well as key livelihood and economic value – $23.3 billion in 2020. It is a water-intensive crop, however, and requires 1,000–2,000 millimeters of irrigation per cropping cycle, contributing to almost 40% of freshwater withdrawals in India. Most irrigation water is abstracted from groundwater, which relies on pumping that has led to a significant decline in the groundwater table in many places. Shifts in cultivation practices and management may foster greater sustainability.